Powdered Sugar Examination as a Tool for the Assessment of Paenibacillus larvae Infection Levels in Honey Bee Colonies - Bassi, Stefano; Galletti, Giorgio; Carpana, Emanuele; Palminteri, Stefano; Bosi, Filippo; Loglio, Giulio; Carra, Elena (Frontiers in Veterinary Science, 2022)
American Foulbrood (AFB) is a contagious and severe brood disease of honey bees caused by the spore-forming bacterium Paenibacillus larvae. The identification of honey bee colonies infected by P. larvae is crucial for the effective control of AFB. We studied the possibility of identifying the infections by P. larvae in honey bee colonies through the examination of powdered sugar samples collected in the hives. The powdered sugar was dusted on the top bars of honeycombs and collected from a sheet paper placed at the bottom of the hive. Three groups of honey bee colonies were examined: Group A1 - colonies with clinical symptoms of AFB (n=11); Group A2 – asymptomatic colonies located in apiaries with colonies showing symptoms of AFB (n=59); Group B – asymptomatic colonies located in apiaries without cases of the disease (n=49). The results showed that there was a significant difference in spore counting between Groups and that the spore load in sugar samples was always consistent with the clinical conditions of the colonies and with their belonging to AFB-affected apiaries or not. Based on the obtained results the cultural examination of powdered sugar samples collected from hives could be an effective tool for the quantitative non-destructive assessment of P. larvae infections in honey bee colonies.